PENGARUH TINGKAT KEPATUHAN PENGENDALIAN INTERN PADA EFEKTIVITAS USAHA KOPERASI SIMPAN PINJAM DI KOTA DENPASAR - Dewi, Putu Sanjita; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2016)
Implementation of activitiys corp has been widely applied to various types of companies, including the non-profit corporation. This is because the implementation of corp is able to affect the company's performance. This reasearchin on companies in Denpasar  the Samples were taken deliberately so as much as 88 used as a sample.. Hypothesis testing results showed that the variables of risk assessment as well as information and communication have a significant effect on the effectiveness of the effort, while the control environment, which means do not affect the effectiveness of the business, while the risk assessment as well as information and communication above the table, which means t affect the effectiveness of the Credit Unions efforts in Denpasar.
Keywords: compliance, effectiveness, cooperative